Laterality and Patient-Reported Outcomes following Autologous Breast Reconstruction with Free Abdominal Tissue: An 8-Year Examination of BREAST-Q Data. Issue 5 (November 2020) - Allen, Robert J.; Sobti, Nikhil; Patel, Aadit R.; Matros, Evan; McCarthy, Colleen M.; Dayan, Joseph H.; Disa, Joseph J.; Mehrara, Babak J.; Morrow, Monica; Pusic, Andrea L.; Nelson, Jonas A.
Abstract : Background: Despite the rise in rates of contralateral prophylactic mastectomy, few studies have used patient-reported outcomes to assess satisfaction between unilateral and bilateral breast reconstruction with autologous tissue. The purpose of this study was to investigate patient satisfaction and quality of life following autologous reconstruction to determine whether differences exist between unilateral and bilateral reconstructions to better guide clinical decision-making. Methods: The current study examined prospectively collected BREAST-Q results following abdominal free flap breast reconstruction procedures performed at a tertiary academic medical center from 2009 to 2017. The reconstruction module of the BREAST-Q was used to assess outcomes between laterality groups (unilateral versus bilateral) at 1 year, 2 years, 3 years, and more than 3 years. Results: Overall, 405 patients who underwent autologous breast reconstruction completed the BREAST-Q. Cross-sectional analysis at 1 year, 2 years, and 3 years revealed similar satisfaction scores between groups; however, bilateral reconstruction patients demonstrated higher satisfaction scores at more than 3 years ( p = 0.04). Bilateral reconstruction patients reported lower scores of abdominal well-being at 1 year, 2 years, and more than 3 years ( p = 0.01, p = 0.03, and p = 0.01, respectively). Conclusions: These results suggest that satisfaction with breasts does not differ with the laterality of the autologous reconstruction up to 3 years postoperatively but may diverge thereafter. Bilateral reconstruction patients, however, have lower satisfaction with the abdominal donor site. These data can be used in preoperative counseling, informed consent, and expectations management in patients considering contralateral prophylactic mastectomy.